In Silico Characterization of Hras Pathway for Therapeutic Implications Against Cancer - Amjad, S.; Naz, A.; A. Malik, M. F. (The Nucleus, 2015)
Hras (v-Ha-ras Harvey rat sarcoma viral oncogene homolog) plays a pivotal role in breast tumorigenesis. Expressional aberrations in Hras has significantly been correlated with patient’s poor overall survival. In the present study, in silico characterization of Hras to trigger downstream effectors including raf, mek, erk has been explored. Three mutational hotspots for Hras (codons12, 13, 61) have been retrieved from the literature. Promoter modelling using Proscan software revealed a promoter region lacking TATA sequence. To study the epigenetic modifications, methylation analysis of promoter lacking TATA box was done using Methylator software. Methylation is directly correlated with tumor targeting therapies as it represses expression of certain oncogenes. Five candidate sites for hypermethylation of Hras were predicted. Analysis of protein residues involved in interlocking with its downstream effector proteins was also uncovered. In addition to this, a diagnostic and therapeutic relevance of micro RNAs (miRNAs/miRs) specifically acting either as oncogene or tumor suppressors on Hras mediated pathway have been identified. Seven micro RNAs (Let-7, miR-195, miR-497, miR- 184, miR-34a, miR-34c, miR-155) found to be responsible for down regulating expression of proteins involved in rassignalling cascade while miR-372 and miR373, miR-212, miR-206/21 and miR17-92 cluster are known to elevate rassignalling pathway. Interestingly, dysregulated expression of Let-7, miR-195, miR-497, miR-184, miR-34, miR-155 co-related with poor prognosis in different cancers has also supported these in silico findings.